Human Bone Marrow-Derived Mesenchymal Cell Reactions to 316L Stainless Steel: An in Vitro Study on Cell Viability and Interleukin-6 Expression - Iwan Budiwan Anwar; Asep Santoso; Eko Saputra; Rifky Ismail; J. Jamari; Emile Van der Heide (Tabriz University of Medical Sciences, 2017)
Purpose: Human bone marrow-derived mesenchymal cell (hBMC) reactions to 316L stainless steel (316L-SS) have never been evaluated. The objective of this study was to assess cell viability and interleukin-6 expression of hBMC cultures upon treatment with a 316L-SS implant. Methods: A cytotoxicity analysis was conducted with a 3-(4,5-dimethylthiazol 2-yl)-2,5-diphenyltetrazolium (MTT) assay after a period of 24, 48 and 72 hours of incubation. Expression of interleukin-6 was measured using enzyme-linked immunosorbent assay (ELISA). Results: Cell viability measurement was performed via IC50 formula. All treatment group showed a > 50 % cell viability with a range of 56,5 - 96,9 % at 24 hours, 51,8-77,3% at 48 hours and 70,1- 120 % at 72 hours. Interleukin-6 expression was downregulated subsequent to treatment with 316L-SS compared to the control group. Conclusion: We found that 316L-SS did not exhibit toxicity towards hBMC culture.